2013
DOI: 10.1186/1471-2156-14-71
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of rice landraces from Eastern and North Eastern States of India

Abstract: BackgroundAdaptations to different habitats across the globe and consequent genetic variation within rice have resulted in more than 120,000 diverse accessions including landraces, which are vital genetic resources for agronomic and quality traits. In India the rice landraces of the states West Bengal, Assam, Mizoram, Manipur and Nagaland are worthy candidates for genetic assessment. Keeping the above in view, the present study was conducted with the aim to (i) calculate the genetic distances among the accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
111
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 35 publications
19
111
3
Order By: Relevance
“…The average PIC value was almost identical using both marker systems, showing the discriminatory power of iPBS-retrotransposon markers. The average PIC value based on the SSR data used in this study was comparable with values from other rice genetic diversity studies, but lower than those reported in studies on rice varieties from Argentina (0.69) that were performed using 28 SSRs (Giarrocco et al, 2007), from India (0.61) using 30 SSRs , from Australia (0.74) using 10 SSRs (Garland et al, 1999), or from India using 23 SSRs among 91 landraces (Das et al, 2013).…”
Section: Discussionsupporting
confidence: 51%
“…The average PIC value was almost identical using both marker systems, showing the discriminatory power of iPBS-retrotransposon markers. The average PIC value based on the SSR data used in this study was comparable with values from other rice genetic diversity studies, but lower than those reported in studies on rice varieties from Argentina (0.69) that were performed using 28 SSRs (Giarrocco et al, 2007), from India (0.61) using 30 SSRs , from Australia (0.74) using 10 SSRs (Garland et al, 1999), or from India using 23 SSRs among 91 landraces (Das et al, 2013).…”
Section: Discussionsupporting
confidence: 51%
“…Several workers also reported that these markers are highly polymorphic (Mohammadi-nejad et al 2008;Karmakar et al 2012;Chattopadhyay et al 2014;Ganie et al 2014). The PCR profile obtained from the SSR markers generated a total of 99 alleles including 20 rare alleles and 16 null alleles, accounting an average of 12.37 alleles/ locus which is higher than the numbers reported by other groups using the SSR markers (Mohammadi-Nejad et al 2008;Islam et al 2012;Karmakar et al 2012;Das et al 2013). Based upon the PIC value, amplicon size range and the number of alleles, RM8094 is advocated to be the most useful and informative marker than others for studying the diversity of Saltol QTL.…”
Section: Discussionmentioning
confidence: 85%
“…The DNA was PCR amplified using a protocol standardized in our lab and used in our previous paper [28]. …”
Section: Methodsmentioning
confidence: 99%